Pengungkapan Corporate Social Responsibility (CSR) sesuai dengan Prinsip Ekonomi Syariah - Muhammad Fiqri; Yaman Yaman (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This study discusses a review of Islamic economic principles towards disclosure of corporate social responsibility (CSR). This study aims to determine whether CSR disclosure indicators in the annual report of PT. Semen Tonasa, Tbk in accordance with sharia economic principles. Research Results Shows disclosure of social responsibility includes economic aspects, social aspects, environmental aspects, aspects of labor, aspects of human rights, and product aspects that occur in the company. Social responsibility in CSR practices for disclosure of CSR activities to the community is very important. This is in accordance with the fundamental principles that shape the philosophy of environmental virtues carried out holistically by the Prophet Muhammad SAW, namely the belief in the interdependence between God's creatures. Islam requires circulation of wealth to occur to all members of society and prevents the circulation of wealth to only a few people. Allah SWT said: